P59 How COVID-19 influenced UK Burns Services: a national multicentred audit. (8th April 2021) - Yoshimura, Ryo; Phillips, Georgina; Wormald, Justin; Collins, Declan
Abstract: Introduction: COVID-19 has affected national guidelines and availability of resources, resulting in different approaches to treating burns. This project aimed to identify changes to burns management in the UK during the "first wave" of COVID-19, and how the lessons learned can be applied to the current "second wave". Methods: Between 11th July-15th September, 18 burns services across the UK completed a MDT survey and contributed data on service evaluation. The MDT survey captured perspectives of multiple stakeholders and included changes to burns services, disruptions to supply chain, and service improvements resulting from COVID-19. Service evaluation data was collected retrospectively and prospectively on patients who received inpatient/outpatient treatment during COVID-19. Patients in the retrospective cohort were first seen by burns services between 6th-30th April (coinciding with the UK's COVID-19 peak), and the prospective cohort were first seen between 30th April-15th September. Each cohort consisted of 10-20 patients per burns service. Service evaluation covered key areas of burns aetiology, referral pathway changes, patient presentation delays to tertiary services, patient management decisions, and outpatient dressing clinic management. Data from the MDT survey and the service evaluation were analysed by descriptive statistics and thematic analysis. Results: The changes to burns services include delays in burn referrals, increase in conservative management, and increased use of telemedicine. Conclusion: Across the UK, safe and effective burns care continued to be delivered despite difficulties from the pandemic. We hope the learning points identified in this study will be of use during the "second wave" of the pandemic.